2011
DOI: 10.1039/c0cp00898b
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of the anthracycline antitumor drugsDoxorubicin and Sabarubicin for human telomeric G-quadruplex structures

Abstract: Combining various techniques in solution we proved that Doxorubicin, also called Adriamycin, and Sabarubicin, also known as MEN 10755, bind to the human telomeric sequence, 5'-d[GGG(TTAGGG)(3)]-3' (21-mer), assuming a G-quadruplex structure in the presence of K(+). Complexes of drugs with the 21-mer in 1 : 1 and 2 : 1 stoichiometry coexist in solution. Association constants were obtained from titration experiments and confirmed by isothermal titration calorimetry. The fluorescence of the drugs was quenched upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 77 publications
7
42
1
Order By: Relevance
“…Anthracyclines, especially DNR and DOX have been widely investigated using various spectroscopic methods, e.g. Raman spectroscopy [24,25], Resonance Raman (RR) [26][27][28], Surface Enhanced Raman Spectroscopy (SERS) [29][30][31][32], UV-Vis absorption [26,33] and FT-IR absorption spectroscopy [24,34,35]. The visible absorption spectra of DOX and DNR are, however, almost identical, having a maximum of absorption near to 480-490 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Anthracyclines, especially DNR and DOX have been widely investigated using various spectroscopic methods, e.g. Raman spectroscopy [24,25], Resonance Raman (RR) [26][27][28], Surface Enhanced Raman Spectroscopy (SERS) [29][30][31][32], UV-Vis absorption [26,33] and FT-IR absorption spectroscopy [24,34,35]. The visible absorption spectra of DOX and DNR are, however, almost identical, having a maximum of absorption near to 480-490 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that doxorubicin (DOX; Scheme ), which is a natural anthracycline compound, can also cause telomere dysfunction for some cellular lines; this effect might arise from the ability of the drug to interact with telomeric G4 . In this respect, it was shown that DOX can form complexes with the human telomeric G4 sequence, 5′‐d[GGG(TTAGGG) 3 ]‐3′ (Tel21), with a comparable affinity to that for B‐DNA ,…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of secondary structures in human DNA, such as B-DNA, Z-DNA, hair pins, etc [5]., guanine rich sequences like, G-quadruplexes serve an important role in cancer cell growth and control gene expression in telomeres [6]. G-quadruplexes are composed of four stranded guanine bases stabilized by monovalent cations such as Na þ or K þ between tetrad guanine bases [7]. Recent studies show that this unique structure can be formed not only in the telomeric region of the genome, but also among other guanine rich sequences having the potential to form quadruplex elsewhere in the human genome [8,9].…”
Section: Introductionmentioning
confidence: 99%